Swept up in uncertainty at PowerSweeping - Littell, Matt (SAGE Business Cases., 2022)
By 2021, Manvendra "Manny" Saxena had acquired three small California street sweeping firms through a search fund and had combined them under the umbrella company PowerSweeping. Consistent with the search fund model, his goal was to streamline PowerSweeping's operations, help it grow, and then one day sell it at a high valuation. That was easier said than done. The three firms that made up PowerSweeping played in two different sweeping subindustries-municipal and construction-which used different equipment, served different types of customers, and had different revenue characteristics. The firms also employed both non-unionized and unionized workers from two unions, which limited Saxena's ability to integrate them. As Saxena generated a strategy, he also faced increased fuel, repair, maintenance, parts, and labor costs in the post-COVID environment, as well as intense competitive pressure from ASC, the largest street sweeping conglomerate in the United States. ASC was eyeing a roll-up merger through California and had made an offer to buy PowerSweeping-though the offer was less than what Saxena believed was its actual value. How could Saxena quickly streamline PowerSweeping and stave off inflation and competition long enough to unlock the company's true value for himself and his investors?